ANALISIS PERANAN BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. FEDERAL INTERNATIONAL FINANCE GROUP - Rini Astriyani; Vina Arisana (Draf Solusi Indonesia, 2024)
In today's fast-paced and highly competitive business environment, companies must continue to improve their performance to remain relevant and competitive, Culture plays an important role in improving employee performance. Therefore, if a company has a good organizational culture, job satisfaction will be high so that it will improve performance. Conversely, if the organizational culture is not good, it will cause a decrease in the performance of individual members and will also affect the performance of the organization. The purpose of this article is to understand and develop a positive organizational culture in improving employee performance. The method of writing a Literature Review article means using the Literature Review method (library research) and Systematic Literature Review (SLR), in qualitative analysis, sourced from the online Google Scholar application, Mendeley and other online academic applications. Organizational Culture defines being the values that guide employees to fulfill the responsibilities resulting from their actions in the organization that indicate whether the action is good or bad, whether the behavior is necessary or not, Employee Performance is the impact of work that can be achieved by a person or group of people in carrying out their duties accordingly, which is a means to achieve organizational goals and agreed success.With a positive organizational culture, employees are more likely to be motivated and satisfied with work